Association between the Endothelial Activation and Stress Index (EASIX) and all-cause and cardiovascular mortality in patients with diabetes and prediabetes - Enfa Zhao; Yiqing Chen; Hang Xie; Ruimeng Wang; Yuan Gao; Bingtian Dong; Chaoxue Zhang (European Journal of Medical Research)
Abstract Background Vascular endothelial impairment is crucial in diabetes and its cardiovascular complications, but clinically applicable endothelial function markers remain limited. We investigated the Endothelial Activation and Stress Index (EASIX), a novel biomarker calculated from lactate dehydrogenase, creatinine, and platelet count, for predicting mortality in diabetes and prediabetes populations. Methods The study analyzed data from 20,285 participants with diabetes or prediabetes enrolled in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. Mortality outcomes were tracked through the National Death Index until December 2019. EASIX was calculated as: lactate dehydrogenase (U/L) × creatinine (mg/dL)/platelet count (109/L). We employed multiple statistical approaches, including Kaplan–Meier survival analysis, multivariable Cox proportional hazards models, restricted cubic spline analysis, and stratified analysis to examine the relationship between EASIX and mortality outcomes. Results During a median follow-up of 90.2 months, 3,432 deaths occurred, including 1,128 cardiovascular-related deaths. Higher EASIX values were significantly associated with increased risks of all-cause and cardiovascular mortality (P for trend < 0.0001). In the fully adjusted model, the highest EASIX quartile (Q4) demonstrated significantly higher risks as compared to the lowest quartile (Q1): all-cause mortality (HR: 1.50, 95% CI 1.33–1.69) and cardiovascular mortality (HR: 1.72, 95% CI 1.38–2.14). Nonlinear relationships were observed between EASIX and mortality outcomes (P for nonlinearity < 0.001). While EASIX predicted outcomes in both populations, diabetic patients showed a more pronounced effect. Subgroup analyses revealed more significant associations in females (HR: 1.36, 95% CI 1.28–1.44) compared to males (HR: 1.18, 95% CI 1.13–1.22), and the association was modified by hypertension status (P for interaction = 0.002). Conclusion EASIX emerges as an independent predictor of all-cause and cardiovascular mortality in diabetes and prediabetes patients. Its accessibility makes it a practical tool for identifying patients requiring intensive monitoring and intervention. The stronger associations in specific subgroups, particularly among diabetic patients and females, underscore the need for targeted approaches.